Analysis and Implementation of Financial Reporting and Tax Obligations for The Sustainability of Village-Owned Enterprises (Case Study of BUMDes Cipayung) - Budianti, Wiwik; Budiman Slamet; Ananda Trifadiya Nur Aqila (PT Inovasi Pratama Internasional, 2025)
The enactment of Government Regulation Number 11 of 2021 reaffirms the role of BUMDes as pillars of economic activities in villages, functioning as both social and commercial institutions. For sustainability, these functions require financial management and compliance. BUMDes, as entities, are corporate taxpayers as they fulfill the two elements of taxation: subjective and objective obligations. The purpose of this research is to analyze the Self-Assessment System at BUMDes Cipayung and determine whether the financial reports used to calculate taxes are in accordance with accounting standards. This study employs a qualitative descriptive method, using income statements as quantitative data, along with research and interviews. The results indicate that BUMDes Cipayung has not yet fulfilled its tax obligations. BUMDes also show errors in recording revenue; therefore, financial statements are not accurate and complete. Inadequate past management accountability is one of the reasons for fulfilling Corporate Income Tax obligations. For 2022 and 2023, BUMDes should be able to calculate and pay Corporate Income Tax using the general income tax rate (Article 31E)